Impact of re-operation on progression-free survival in patients with recurrent GBM: Experience in a tertiary referral center - Houssein Darwish; Tasnim Diab; Sarah Kawtharani; Mounir Barake; Bader Ali; Nagham Ramadan; Hiba Fadlallah; Jeannot Kekedjian; Marwan Najjar; Hazem I. Assi (PLoS ONE, 2025)
Background Reoperation for patients with recurrent glioblastoma multiforme (GBM) is a highly debated topic within the medical community. GBM is known for its aggressive nature and poor prognosis, with most patients experiencing tumor recurrence despite initial treatments. Some studies suggest a survival benefit from a second surgery, while others do not. The aim of this study is to assess whether reoperation for recurrent GBM offers a survival benefit compared to patients who do not undergo re-resection and to identify the prognostic factors influencing patient selection for reoperation. Methods This study retrospectively reviewed medical records from the American University of Beirut Medical Center over a ten-year period, from 01/01/2012 to 01/01/2023. It included patients with recurrent GBM after initial surgical resection. Patients were categorized into two groups: those who underwent reoperation and those who received only medical management upon recurrence. Inclusion criteria included histologically confirmed GBM with previous tumor resection; patients who only had a biopsy were excluded. Time to progression and time to death were analyzed using the Kaplan-Meier curve, with differences between groups assessed by the log-rank test. Results Age categorization (≤50 vs. >50 years) and gender distribution did not significantly impact reoperation likelihood (p = 0.306 and p = 0.616, respectively). However, a notable association was observed with Charlson comorbidity index (CCI) ≤3, indicating higher reoperation rates (p = 0.022). Tumor size grouping (≤5 vs. >5 cm) showed no significant association with reoperation status (p = 0.175). Similarly, whether the tumor was unifocal or multifocal and the extent of initial tumor resection (GTR vs. subtotal) did not demonstrate significant associations with reoperation (p = 0.086 and p = 0.351, respectively). Remarkably, complications following the initial surgery emerged as a significant factor associated with the decision not to undergo reoperation (p = 0.018). The most common complications following both initial and subsequent surgeries included DVT, weakness, seizures, and wound leakage and infection. The progression-free survival for patients who underwent reoperation was 15.9 months, whereas for those who did not undergo reoperation, it was 6.7 months (log-rank p < 0.001) The median post progression survival for patients who underwent reoperation upon recurrence was 5.9 months, compared to 5.1 months for those who did not undergo reoperation. (log-rank p = 0.065). The median overall survival for patients who did not undergo reoperation was 11 months, compared to 21 months for those who underwent reoperation (log-rank p < 0.001). Conclusion In conclusion, reoperation for recurrent Glioblastoma Multiforme (GBM) appears to offer a survival benefit, as indicated by significantly longer disease-free intervals and higher progression-free and overall survival rates compared to patients who did not undergo reoperation.